Does wealth increase affect school enrolment in ultra-poor households: Evidence from an experiment in Bangladesh - Sulaiman, Munshi (Practical Action Publishing, 2022)
This article was published in The Enterprise Development & Microfinance and the definite version is available at: DOI:10.3362/1755-1986.2015.014 The Article's website is at: https://practicalactionpublishing.com/article/2359/does-wealth-increase-affect-school-enrolment-in-ultra-poor-households-evidence-from-an-experiment-in-bangladesh